Stabilization of Time‐Varying and Disturbed Complex Dynamical Networks with Different‐Dimensional Nodes and Uncertain Nonlinearities. Issue 6 (8th May 2017) - Zhang, Lili; Lei, Youfa; Wang, Yinhe; Chen, Baoying
Abstract: This paper investigates the stabilization problem for time‐varying and disturbed complex dynamical networks (CDNs) with different‐dimensional nodes and uncertain nonlinearities. To be consistent with the properties of real‐world networks, both the disturbances of our networks and the nonlinear structures of the nodes permit are completely unknown but bounded. Furthermore, the norm bounds of the uncertain nonlinearities and disturbances (NBUND) are applied to design the stabilization controllers. When the NBUND are known in advance, some decentralized state feedback controllers are proposed to stabilize our networks. And when they are unknown, adaptive decentralized stabilization schemes are brought forward for our network models. The effectiveness and feasibility of our theoretical results are verified by two simulation examples.